2002
DOI: 10.1016/s0029-7844(02)02246-9
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy, labor, delivery, and pelvic organ prolapse1

Abstract: Our data suggest that elective cesarean is only partially effective in preventing pelvic organ prolapse. Cesarean delivery during active labor and vaginal delivery had a similar effect on the maternal pelvic support. This indicates that prolapse developed during the first and not the second stage of labor. Black women are as susceptible to developing prolapse during childbirth as their white counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(30 citation statements)
references
References 19 publications
2
27
1
Order By: Relevance
“…Similar to other authors [14,16,18], we observed a low prevalence of prolapse after cesarean section. We found prolapse stage ≥II in only 4 (7.7%) women who had undergone cesarean sections.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Similar to other authors [14,16,18], we observed a low prevalence of prolapse after cesarean section. We found prolapse stage ≥II in only 4 (7.7%) women who had undergone cesarean sections.…”
Section: Discussionsupporting
confidence: 92%
“…Using POPQ measurements, Dannecker et al [17] indicated more evidence of anterior vaginal wall descent after vaginal delivery in comparison with a nulliparous control group. Sze et al [16] reported that 97% of the 78 women with POP 6 weeks postpartum had the more severe defect in the anterior vaginal wall. Handa et al [18] also found a trend toward poorer support of the anterior vaginal wall in the vaginal delivery cohort as compared to cesarean without labor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations